Elucidating the regulatory roles of microRNAs in maize (Zea mays L.) leaf growth response to chilling stress - Aydinoglu, Fatma (Springer, 2020)
Main conclusion miRNAs control leaf size of maize crop during chilling stress tolerance by regulating developmentally important transcriptional factors and sustaining redox homeostasis of cells. Chilling temperature (0-15 degrees C) is a major constraint for the cultivation of maize (Zea mays) which inhibits the early growth of maize leading to reduction in leaf size. Growth and development take place in meristem, elongation, and mature zones that are linearly located along the leaf base to tip. To prevent shortening of leaf caused by chilling, this study aims to elucidate the regulatory roles of microRNA (miRNA) genes in the controlling process switching between growth and developmental stages. In this respect, hybrid maize ADA313 seedlings were treated to the chilling temperature which caused 26% and 29% reduction in the final leaf length and a decline in cell production of the fourth leaf. The flow cytometry data integrated with the expression analysis of cell cycle genes indicated that the reason for the decline was a failure proceeding from G2/M rather than G1/S. Through an miRNome analysis of 321 known maize miRNAs, 24, 6, and 20 miRNAs were assigned to putative meristem, elongation, and mature zones, respectively according to their chilling response. To gain deeper insight into decreased cell production, in silico, target prediction analysis was performed for meristem specific miRNAs. Among the miRNAs, miR160, miR319, miR395, miR396, miR408, miR528, and miR1432 were selected for confirming the potential of negative regulation with their predicted targets by qRT-PCR. These findings indicated evidence for improvement of growth and yield under chilling stress of the maize.
Keywords: Chilling tolerance; Leaf size; Maize microRNAs; miRNome; Organ growth; Plant cell cycle